Chapter Un passo ulteriore verso un sistema federale: un tributo per l'Unione Europea - BIZIOLI, Gianluigi (Studi e saggi, 2022)
Attempts to adapt the idea of sovereignty in order to understand the phenomenon of European integration inevitably lead to two opposing theoretical representations: on the one hand, to configure European integration as a process derived from and legitimised by state sovereignty; on the other hand, on the contrary, to consider the European Union as the locus of sovereign legitimation and that this radiates out over the member states. These reconstructions are inadequate: on the one hand, they employ a notion of sovereignty that does not fit the plural organisations of state, and, in particular, the idea of federalism, and, on the other hand, they were unable to valorise the original features of the EU system, its functioning and relations with the member states. The aim is to investigate the prerequisites and limits of the Union's tax power and, to this end, the question of the (preferable) qualification of the Union will be addressed first; then, that of the contents and boundaries of the Union's tax competences in order to verify the ownership of a power to introduce own taxes, having regard to the regulatory function of the Union and the instrumental function for the establishment and functioning of the Economic and Monetary Union (EMU).